2018
DOI: 10.1371/journal.pone.0208929
|View full text |Cite
|
Sign up to set email alerts
|

Annotated 18S and 28S rDNA reference sequences of taxa in the planktonic diatom family Chaetocerotaceae

Abstract: The species-rich diatom family Chaetocerotaceae is common in the coastal marine phytoplankton worldwide where it is responsible for a substantial part of the primary production. Despite its relevance for the global cycling of carbon and silica, many species are still described only morphologically, and numerous specimens do not fit any described taxa. Nowadays, studies to assess plankton biodiversity deploy high throughput sequencing metabarcoding of the 18S rDNA V4 region, but to translate the gathered metaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 54 publications
6
63
0
Order By: Relevance
“…Gaonkar et al . () showed that a phylogeny inferred from the V4 region of Chaetocerotaceae corroborates those inferred from the 18S and partial 28S rDNA regions and that virtually all species are distinguishable. Species identification of the inferred taxa is also straightforward because of the availability of an extensive 18S rDNA reference sequence database (for morphology of the reference strains, see Supporting Information figs.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Gaonkar et al . () showed that a phylogeny inferred from the V4 region of Chaetocerotaceae corroborates those inferred from the 18S and partial 28S rDNA regions and that virtually all species are distinguishable. Species identification of the inferred taxa is also straightforward because of the availability of an extensive 18S rDNA reference sequence database (for morphology of the reference strains, see Supporting Information figs.…”
Section: Introductionmentioning
confidence: 67%
“…Species identification of the inferred taxa is also straightforward because of the availability of an extensive 18S rDNA reference sequence database (for morphology of the reference strains, see Supporting Information figs. 1–44 of Gaonkar et al ., ; see also e.g., Balzano et al ., ; Li et al ., ). We compared phylogenetically inferred taxa with OTUs obtained using clustering to explore how the two methods perform.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Gaonkar et al. ) and, where possible, to identify diagnostic morphological features. In this way, our results feed directly into the international open‐access barcoding library Diat.barcode (Rimet et al.…”
mentioning
confidence: 99%